Quarterlife Crisis in Popular Literature: Riffaterrian Semiotics Analysis on Neck Deep's ‘All Distortions Are Intentional’ Album - Faldiaz, Muhammad; Ruminda, Ruminda; Sakinah, R. Myrna Nur (Journal of English Language and Education, 2025)
All Distortions Are Intentional is an album from Neck Deep, which was released in 2020. The album consists of twelve songs that explore various themes, including the quarterlife crisis phenomenon. The research seeks to analyse the depiction of the quarterlife crisis phenomenon as experienced by the character through the theory of Michael Riffaterre's semiotics theory, emphasising two key approaches: 1) heuristic and hermeneutic reading, and 2) indirect expression. This research employs a qualitative approach, emphasising content analysis. This research employed content analysis to analyse the song lyrics from All Distortions Are Intentional album. This research identifies that the depiction of quarterlife crisis in All Distortions Are Intentional album presents in only three songs: Sonderland, Telling Stories, and Sick Joke. Those songs depict the quarterlife crisis through hermeneutic reading and indirect expression. Displacing of meaning consists of four data, while distorting of meaning and creating of meaning consist of three data that depict the quarterlife crisis phenomenon.